â€œWhat Happen Next?â€ Strategy to Improve Students Skill on Writing Narrative Text - Sri Wahyuni (Universitas Hamzanwadi, 2017)
Most of the EFL learners, especially at senior high schools, frequently consider that writing is the most difficult skill compared to the three other language skills. This difficulty was also faced by the second year students of Madrasah Aliyah Muhammadiyah Malang. The results of their writing performance at the preliminary research indicated that on average they achieved low grades in writing narrative texts. Moreover, the students in this school were not motivated in writing. For this case, the writer applied a strategy â€œwhat happen next?â€ which can improve the skill in writing narrative texts. The strategy was implemented in action research through four steps: planning, implementing, observing, and reflecting. The action research was conducted in two cycles and involves 24 students. The results of the findings showed the improvement of the studentsâ€™ skill in writing narrative texts and also the improvement of the studentsâ€™ involvement in the writing activities during the teaching and learning process.